2022
DOI: 10.1016/j.scitotenv.2021.150139
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging Google Earth Engine platform to characterize and map small seasonal wetlands in the semi-arid environments of South Africa

Abstract: There is a great concern that small semiarid wetlands are not routinely monitored.• Monitoring of small wetlands using optical data has remained a challenge. • Google Earth Engine platform was used to study small wetlands in Limpopo. • Google Earth Engine provides new opportunities to improve wetlands monitoring. • Findings underscore the relevance of GEE in studying small and seasonal wetlands.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 44 publications
1
24
0
Order By: Relevance
“…Seasonal wetlands, with high heterogeneity of temporal and spatial changes, have more abundant ecological functions and higher biodiversity than permanent wetlands [ 50 , 51 ]. Figure 8 shows the spatiotemporal dynamic changes in the seasonal wetlands at the three Dongting Lake wetland reserves, by overlaying the mapping results of the seasonal wetlands from 2000 to 2020.…”
Section: Resultsmentioning
confidence: 99%
“…Seasonal wetlands, with high heterogeneity of temporal and spatial changes, have more abundant ecological functions and higher biodiversity than permanent wetlands [ 50 , 51 ]. Figure 8 shows the spatiotemporal dynamic changes in the seasonal wetlands at the three Dongting Lake wetland reserves, by overlaying the mapping results of the seasonal wetlands from 2000 to 2020.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, the GEE has been used in a variety of fields, from geology and biology to ecology, with varying levels of success [22,23]. Different applications have used the GEE to map the current distribution or the change detection of both large and small wetland dynamics [24][25][26][27][28], which indicates a great potential of the GEE for different scale mapping of wetland ecosystems. Despite this, almost all research requires complex input data (i.e., data transformation, LiDAR, and multi-source datasets), varying in classification accuracy (85-97%), and leverages the powerful prediction of the ML boosting algorithm to different extents.…”
Section: Introductionmentioning
confidence: 99%
“…Today, with the development of cloud-based platforms such as Google Earth Engine (GEE), it has been possible to process remote sensing data online without downloading [20]. Various studies showed the effectiveness of GEE in different remote sensing applications such as landcover classification [21,22], wetland detection [23], water quality monitoring [24], flood mapping [19], and impact analysis of drought and floods on croplands [25].…”
Section: Introductionmentioning
confidence: 99%